Dari BPUPKI ke Pancasila: Refleksi Sejarah Pembentukan Negara dan Pendidikan Kewarganegaraan di Indonesia - Kurniasih, Maulana Dwi; Isma’il, Muhammad (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This article explores the historical journey of the formation of the Indonesian state, starting from the role of BPUPKI (The Investigating Committee for Preparatory Work for Indonesian Independence) to the formulation of Pancasila as the nation's foundational ideology. BPUPKI, established in 1945, played a key role in preparing Indonesia's independence and formulating the inclusive foundations of the state, including through the Jakarta Charter. Pancasila, with its five principles, was designed to unite Indonesia's diverse cultures, religions, and ethnicities. This article uses a mixed-methods approach, including historical analysis of primary and secondary sources to understand the process of Pancasila’s formulation, as well as qualitative research on the practice of civic education. The focus of this study is on how Pancasila’s values are taught and internalized by students, as well as the challenges faced in maintaining the relevance of civic education amidst the development of globalization and technology. The article concludes that the foundational ideology, Pancasila, plays an important role in maintaining Indonesia's pluralistic unity while balancing the preservation of traditional values and accommodating the changing times in civic education, ensuring that these principles remain relevant and strengthen the unity of the Indonesian nation amid ongoing global dynamics.